Multi-scale material/structure integrated elastic metamaterial for broadband vibration absorbing - Xingzhong Wang; Chao Zhang; Shiteng Rui; Chengjun Wu; Weiquan Zhang; Fuyin Ma (Materials & Design, 2024)
To break the high additional mass ratio requirement of traditional vibration absorbing materials/devices, and overcome the shortcoming of the narrow operating frequency band of conventional local resonance metamaterial dampers, this paper proposes a lightweight multi-scale material/structure integrated elastic metamaterial for broadband vibration absorption. By replacing the mass components in the macroscopic metamaterial vibration absorber with a composite mass body filled with microscopic particle materials, a multi-scale structure/material integrated design between the macroscopic oscillator and microscopic particle is realized. The macroscopic oscillator absorbs low-frequency vibration, while the microscopic particle cluster absorbs medium–high frequency vibration, thereby achieving a broadband vibration absorption covering the low-medium–high ranges. Based on the band gap theory and the multiphase flow theory of gas-particle, this paper systematically analyzes the band gap effect of multi-scale metamaterials and the dissipation capacity of medium–high frequency caused by particle damping. The structure exhibits commendable vibration damping performance. The multi-scale integrated vibration damper retains the lightweight and sub-wavelength characteristics of the traditional local resonance unit cells, while greatly broadening the working bandwidth, and having potential applications in low-frequency broadband vibration reduction of various mechanical equipment.